A Prognostic Model to Assess Long-Term Survival of Patients on Antiretroviral Therapy: A 15-Year Retrospective Cohort Study in Southwestern China. (12th June 2021) - Jiang, He; Zhu, Qiuying; Feng, Yi; Huang, Jinghua; Yuan, Zongxiang; Zhou, Xinjuan; Lan, Guanghua; Liang, Hao; Shao, Yiming
Abstract: Background: Because there is no assessment tool for survival of people with human immunodeficiency virus (PWH) who received antiretroviral therapy (ART) in rural southwestern China, we aimed to formulate and validate a simple-to-use model to predict long-term overall survival at the initiation of ART. Methods: In total, 36 268 eligible participants registered in the Guangxi autonomous region between December 2003 and December 2018 were enrolled and randomized into development and validation cohorts. Predictive variables were determined based on Cox hazard models and specialists' advice. Discrimination, calibration, and clinical utility were measured, respectively. Results: The prognostic combined 14 variables: sex, age, marital status, infectious route, opportunistic infection, acquired immunodeficiency syndrome (AIDS)-related symptoms, body mass index, CD4 + T lymphocyte count, white blood cell, platelet, hemoglobin, serum creatinine, aspartate transaminase, and total bilirubin. Age, aspartate transaminase, and serum creatinine were assigned higher risk scores than that of CD4 + T lymphocytopenia count and having opportunistic infections or AIDS-related symptoms. At 3 time points (1, 3, and 5 years), the area under the curve ranged from 0.75 to 0.81 and the Brier scores ranged from 0.03 to 0.07. The decision curve analysis showed an acceptable clinical net benefit. Conclusions: The prognostic model incorporating routine baseline data can provide a useful tool for early risk appraisal and treatment management in ART in rural southwestern China. Moreover, our study underscores the role of non-AIDS-defining events in long-term survival in ART. Abstract : A prognostic model comprising 14 variables is an effective tool for early assessing the prognosis of patients in ART. A nomogram for the prognostic model can be printed on paper and is especially suitable for physicians in rural southwestern China.